2009
DOI: 10.1017/s0033291709991966
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use and childhood trauma interact additively to increase the risk of psychotic symptoms in adolescence

Abstract: BackgroundAdolescent cannabis use has been shown in many studies to increase the risk of later psychosis. Childhood trauma is associated with both substance misuse and risk for psychosis. In this study our aim was to investigate whether there is a significant interaction between cannabis use and childhood trauma in increasing the risk for experiencing psychotic symptoms during adolescence.MethodPsychiatric interviews using the Schedule for Affective Disorders and Schizophrenia for School-Age Children (K-SADS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
4
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(145 citation statements)
references
References 55 publications
4
133
4
4
Order By: Relevance
“…Recent evidence has shown that childhood trauma is a risk factor for the development of schizophrenia [42][43][44] and psychotic symptoms. 45 Although several previous studies have suffered from methodological limitations, such as small, highly selected samples and nonstandardized measures of trauma, a recent study has sought to overcome these problems.…”
Section: Childhood Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has shown that childhood trauma is a risk factor for the development of schizophrenia [42][43][44] and psychotic symptoms. 45 Although several previous studies have suffered from methodological limitations, such as small, highly selected samples and nonstandardized measures of trauma, a recent study has sought to overcome these problems.…”
Section: Childhood Traumamentioning
confidence: 99%
“…44 Both cannabis use and childhood trauma, however, additively interacted to increase the likelihood of psychotic symptoms in adolescence to a much greater extent than either risk factor independently. This indication of environmental factors working together to produce a synergistic effect on risk has been found in other studies.…”
Section: Childhood Traumamentioning
confidence: 99%
“…Por ejemplo, estudios epidemiol贸gicos han encontrado que la iniciaci贸n en el uso de cannabis en la adolescencia incrementa la probabilidad de s铆ntomas y trastornos psic贸ticos en la edad adulta (Arseneault et al, 2002) y favorece su persistencia en el tiempo (Mackie et al, 2013). Del mismo modo, parece ser que si el consumo de cannabis interact煤a con otros factores de riesgo como son las experiencias traum谩ticas, aumenta la probabilidad de presencia de s铆ntomas psic贸ticos (Cougnard et al, 2007;Harley et al, 2010). Otros modelos, basados en estudios animales, tambi茅n postulan sobre el efecto que los cannabinoides puedan ocasionar en diferentes receptores dopamin茅rgicos y/o cannabinoides (especialmente a nivel del c贸rtex prefrontal, estriado e hipocampo), as铆 como acerca de su capacidad de generar modificaciones en el sistema glutamat茅rgico e inducir una cascada de cambios bioqu铆mi-cos, tal vez neurot贸xicos, y de igual forma, incrementando el riesgo de desarrollar trastornos psic贸ticos (Bossong y Niesink, 2010;Rocchetti et al, 2013).…”
Section: Discusi贸n Y Conclusionesunclassified
“…Another population registry-based study found that family history of schizophrenia increased both the risk of schizophrenia and of acute cannabis-induced psychosis [25]. A history of child abuse (including sexual, physical, and/or emotional abuse) or neglect also increases the risk of developing schizophrenia after cannabis use [26][27][28][29][30][31]. Two large, population-based, longitudinal studies, in Greece and the Netherlands, both replicated findings that childhood maltreatment and cannabis use precede and are independently associated with increased risk of later psychosis, and that the combination of the 2 risk factors is synergistically associated with an increased risk of psychosis [28].…”
Section: Vulnerability Factorsmentioning
confidence: 99%